Lactarius indohirtipes and L. sharmai (Russulales, Basidiomycota): two novel species from Jammu and Kashmir, India - Verma, Komal; Ahamed, Masood; Kumar, Anil; Mehmood, Tahir; Uniyal, Priyanka (European Journal of Taxonomy, 2024)
Exploration of macrofungi in the Jammu and Kashmir regions, India, led to the discovery of two novel species, described herein as Lactarius indohirtipes sp. nov. and L. sharmai sp. nov. This paper presents detailed morphological descriptions and illustrations, as well as a phylogenetic analysis based on nrITS sequences. A comparative analysis with related species is also included.